Antimicrobial Thiol–ene–acrylate Photosensitive Resins for DLP 3D Printing. (22nd April 2019) - Li, Zhiquan; Wang, Chong; Qiu, Wanwan; Liu, Ren
Abstract: Designing digital light processing (DLP) 3D printable photosensitive resins with antibacterial properties is especially vital because of their potential applications in various biomedical fields. In this contribution, a thiol–ene–acrylate ternary system with reduced volume shrinkage and fast photopolymerization rate was chosen as the antibacterial 3D printing matrix resin. Two quaternary ammonium salt‐type antibacterial agents (QAC and SH‐QAC) with different molecular weight were designed and prepared, which can participate in the curing of matrix resin to achieve contact antibacterial effect. The effects of antibacterial agent content on the photopolymerization kinetics and on thermal and mechanical properties were discussed in detail. When the amount of added QAC is 4wt%, the antibacterial rate is almost 100% for Escherichia coli and Staphylococcus aureus, and when the amount of SH‐QAC is 10wt%, the antibacterial rate against S. aureus is also essentially 100%. Both antibacterial photosensitive resins have been successfully applied in DLP technology to fabricate tooth model with high precision. Abstract : Thiol–ene–acrylate photosensitive resins with contact antimicrobial properties were successfully applied to DLP 3D printing to fabricate object with high resolution.